(untitled) (Global Journal of Human-Social Science, 2023)
Dhaka is one of the most densely populated megacities of the world with demography of over 20 million people With an annual population growth rate of 4 2 Dhaka is set to face the challenges of habitat crisis lack of communal facilities and constant pressure on transportation and infrastructure In response to the demand of the rapidly growing population and scarcity of developable land urban consolidation through vertical expansion was carried out without any proper diagnosis of the sites or any contextually appropriate densification policy The unguided nature of densification not only brought a transformation in the urban landscape but also in the built form itself by infusing the concept of compactness into them The compactness of multistoried dwellings is often found to compromise with the livability condition posing questions on residential sustainability Drawing on three residential areas of varied density age and settlement type this paper therefore attempts to investigate the trend of densification of the densifying residential areas of Dhaka in terms of the spatial quality of the built form its effect on the built environment Key methods of data collection employed extensive field surveys observations measurements map analysis satellite imagery analysis interviews with officials and block surveys for detailed analysis of FAR land coverage in plot and block level height land use pattern and other design aspects of the built form The survey findings were analyzed through descriptive statistical methods including frequency distribution and presented through tables charts and cross-analysis charts contributing to a better understanding of the ongoing trend of densification